2022
DOI: 10.1002/admi.202201079
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Approach to Create Nanobubbles on Arbitrary Two‐Dimensional Materials for Imaging Exciton Localization

Abstract: Strained 2D materials with lattice deformation have the optimal band structure, lattice vibration, and thermal conductivity and various methods have been proposed to introduce strain into 2D materials. However, the creation of localized strain in arbitrary 2D materials in predesigned areas is difficult and challenging. Herein, a versatile approach to creating on‐demand nanobubbles on five different 2D materials using a functional atomic force microscopy (AFM) tip is described. Strain‐induced redshifts are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The halo-like phenomenon presented here coincides with a growing body of evidence for localized strain effects occurring at the periphery of nanobubbles in 2D materials. Chen et al observed a “doughnut-like” pattern in nanophotoluminescence maps of exciton emission in WS 2 nanobubbles, which they attribute to localized inhomogeneous elastic strain and the associated carrier funneling effect . Using valence force field simulations and tight-binding electronic-state calculations, Carmesin et al modeled the spatial distributions of strain and electronic states in TMD nanobubbles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The halo-like phenomenon presented here coincides with a growing body of evidence for localized strain effects occurring at the periphery of nanobubbles in 2D materials. Chen et al observed a “doughnut-like” pattern in nanophotoluminescence maps of exciton emission in WS 2 nanobubbles, which they attribute to localized inhomogeneous elastic strain and the associated carrier funneling effect . Using valence force field simulations and tight-binding electronic-state calculations, Carmesin et al modeled the spatial distributions of strain and electronic states in TMD nanobubbles.…”
mentioning
confidence: 99%
“…Chen et al observed a "doughnut-like" pattern in nanophotoluminescence maps of exciton emission in WS 2 nanobubbles, which they attribute to localized inhomogeneous elastic strain and the associated carrier funneling effect. 45 Using valence force field simulations and tight-binding electronic-state calculations, Carmesin et al modeled the spatial distributions of strain and electronic states in TMD nanobubbles. They showed that bubbles in monolayer MoS 2 should exhibit strong carrier localization in their peripheries due primarily to nonuniform strain and the corresponding bond deformations, which alter the bandgap and confinement potentials.…”
mentioning
confidence: 99%